Miniature moss gardens : create your own Japanese container gardens - Oshima, Megumi; Kimura, Hideshi (Tuttle Publishing, 2017)
Moss can inspire gardeners and non-gardeners alike due to its variety of colors and textures. Oshima and Kimura offer expert advice and techniques to provide ideas and tips, from collecting moss and choosing soil and containers to designing a terrarium with a variety of design elements.